IMPLEMENTASI PERMENDIKBUD NO. 62 TAHUN 2014 TENTANG KEGIATAN EKSTRAKURIKULER KEAGAMAAN (STUDI ANALISIS DESKRIPTIF DI SDN 138 GEGERKALONG, SMPN 15 BANDUNG, DAN SMAN 15 BANDUNG) - Annisa Dwiseptiana Raskania, - (2019)
Efforts to foster students through religious extracurricular activities in schools become a support for the achievement of the objectives of Islamic education. To maintain the existence of religious extracurricular presence in schools, researchers consider the need for good management. Therefore, it is necessary to have a reference that explains how religious extracurricular activities should be carried out. The education sector government has issued technical guidelines on extracurricular activities for elementary, junior high and high school levels. Each technical guide has been adapted to the situation in the school. Therefore, for the sake of running a good and correct religious extracurricular activity it is necessary for the school to pay attention to all aspects in the technical guidelines for each school level. This study uses a qualitative approach with descriptive methods with the type of case study method. Researchers used interview, observation and documentation techniques to obtain the required data. The results of this study indicate that most of the aspects contained in the Technical Guide for Extracurricular Activities in Schools have been implemented in religious extracurricular activities at SDN 138 Gegerkalong, SMPN 15 Bandung, and SMAN 15 Bandung. As for aspects that have not been implemented, including at the planning activities stage at SDN 138 Gegerkalong and SMPN 15 Bandung there is no specific budget design for extracurricular diversity, and at the evaluation stage at these three schools there is no reference in setting assessment standards